2017
DOI: 10.1080/02813432.2017.1333307
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasonography in Norwegian out-of-hours primary health care

Abstract: ObjectiveThe objective of this study is to determine the extent of ultrasound availability in Norwegian casualty clinics and estimate the prevalence of its use.DesignA retrospective study based on a national casualty clinic registry and data from reimbursement claims.SettingOut-of-hours primary health care in Norway.SubjectsAll Norwegian casualty clinics in 2016 and reimbursement claims from 2008 to 2015.Main outcome measuresPercent of casualty clinics with ultrasound, types of ultrasound devices and probes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…There was no observed gender difference between GPs in terms of number of scanning GPs. These results differ from the results described by Myhr et al in out-of-hours clinics [16], where 74% of scanning GPs were men. The difference may be explained by more male GPs working out-of-hours.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There was no observed gender difference between GPs in terms of number of scanning GPs. These results differ from the results described by Myhr et al in out-of-hours clinics [16], where 74% of scanning GPs were men. The difference may be explained by more male GPs working out-of-hours.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed 16% of Norwegian GPs claiming reimbursement for 2012, which confirms the first observation. A study of Norwegian out-of-hours practices in 2016 reported that 23% of practices had POCUS available [16], with 6.5% of physicians scanning in comparison to 30% during office hours. The discrepancies in scanning among physicians between regular office hours and out-of-hours practice cannot be explained by our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Norway, 23% of emergency primary care centres had access to their own ultrasound machines in 2015. However, only 1 of 15 of the GPs working there used ultrasound ever and only 0.3% of billings included an ultrasound item [13]. Ultrasound was in 2014 commonly used in Germany (about 45%) and Greenland (about two-thirds), while it was less commonly used in Sweden, Denmark, Austria, and Catalonia (< 1%) [14].…”
Section: Resultsmentioning
confidence: 99%
“…In emergency departments, abdominal pain is the third most common indication of POCUS [ 5 , 6 , 7 , 8 , 9 ]. Acute abdomen is a sudden onset of abdominal pain that requires immediate medical attention [ 10 ], but is also a major diagnostic challenge with many differential diagnoses that can range from self-limiting illnesses to life-threatening conditions [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%